Allocation of Education Funds and Educational Inequality in the Least Developed, Frontier, and Outermost Regions of East Nusa Tenggara - Joko Susanto; Adinda Bintang Khairunnisa; Mellyana Safitri (Jurnal Informatika Ekonomi Bisnis, 2026)
This study aims to analyze the effect of education funding allocation on educational inequality, with poverty rates and gender gap as control variables, in the least developed, frontier, and outermost regions of East Nusa Tenggara during the 2018-2024 period. The research data are secondary, sourced from the Central Statistics Agency and the Regional Education Balance Sheet, and are in panel form. This study uses panel-data regression analysis with a fixed-effects approach and quantile regression. The results show that although the allocation of education funding reduces educational inequality, it has no effect on the moderate inequality group. Meanwhile, poverty rates have a positive effect on educational inequality in both moderate and extreme groups. The gender gap has no effect on educational inequality, but in the moderate education inequality group, it has a positive effect on educational inequality in the least developed, frontier, and outermost regions of East Nusa Tenggara.